الأمن القانوني وتطبيقاته في المادة الجزائية - خولة روابح; سعاد باجوج (My University, 2025)
Abstract This memorandum examines and analyzes the principle of legal certainty as one of the fundamental pillars of the rule of law, particularly in the field of criminal law, which directly affects the core of individual rights and freedoms. Legal certainty entails that the law be stable, clear, and accessible, enabling individuals to anticipate its legal effects when acting, and providing protection against sudden changes or ambiguous interpretations. The study focused on the applications of legal certainty within criminal law, particularly in terms of the formulation and stability of penal rules, and the safeguarding of fundamental principles such as the principle of legality in criminal matters, the prohibition of retroactive application of harsher criminal laws, and the guarantee of fair trial rights. The study adopted a descriptive and analytical methodology, through the analysis of the Constitution and relevant legislation concerning legal certainty. The findings indicate that achieving legal certainty in the criminal domain requires deep legislative reform, consistent judicial adherence to the principle of legal predictability, and the explicit incorporation of this principle into constitutional provisions to ensure more effective protection of rights and freedoms. ....................... الملخص تتناول هذه المذكرة بالدراسة والتحليل مبدأ الأمن القانوني باعتباره أحد الركائز الأساسية لدولة القانون، خاصة في مجال القانون الجزائي الذي يمس جوهر الحقوق والحريات الفردية. ويُقصد بالأمن القانوني أن يكون القانون مستقرًا، واضحًا، ومعلوماً، بحيث يتمكن الأفراد من توقع أثره القانوني عند التصرف، وتُضمن لهم الحماية ضد التعديلات المفاجئة أو التأويلات الغامضة. وقد ركزت الدراسة على تطبيقات الأمن القانوني في المادة الجزائية، من حيث صياغة القواعد العقابية، استقرارها، وضمان احترام المبادئ الأساسية مثل مبدأ الشرعية الجنائية، وعدم رجعية القوانين العقابية الأشد، وضمان المحاكمة العادلة. اعتمدت الدراسة على المنهج الوصفي التحليلي، من خلال تحليل الدستور و القوانين المتعلقة بالأمن القانوني وخلصت الدراسة إلى أن تحقيق الأمن القانوني في المجال الجزائي يتطلب إصلاحًا تشريعيًا عميقًا، وتكريسًا قضائيًا يحترم مبدأ اليقين القانوني، إضافة إلى إدماج هذا المبدأ ضمن المبادئ الدستورية الصريحة لحماية الحقوق والحريات بشكل أكثر فعالية. .......................... Résumé : La présente mémoire étudie et analyse le principe de la sécurité juridique en tant que l’un des piliers fondamentaux de l’État de droit, notamment dans le domaine du droit pénal qui touche au cœur des droits et libertés individuels. La sécurité juridique implique que la loi soit stable, claire et prévisible, de manière à permettre aux individus d’anticiper ses effets juridiques lorsqu’ils agissent, tout en leur garantissant une protection contre les modifications soudaines ou les interprétations ambiguës. L’étude s’est concentrée sur les applications de la sécurité juridique en matière pénale, notamment en ce qui concerne la formulation des règles répressives, leur stabilité, ainsi que le respect des principes fondamentaux tels que le principe de la légalité criminelle, la non-rétroactivité des lois pénales plus sévères, et le droit à un procès équitable. Cette recherche s’appuie sur une méthode descriptive et analytique, à travers l’analyse de la Constitution et des lois relatives à la sécurité juridique. L’étude conclut que la réalisation de la sécurité juridique dans le domaine pénal exige une réforme législative en profondeur, une consécration judiciaire du principe de sécurité juridique, ainsi que son intégration explicite parmi les principes constitutionnels afin d’assurer une protection plus efficace des droits et libertés.
Keywords: Keywords: Legal certainty; criminal law; principle of legality; procedural legality; الكلمات المفتاحية: الأمن القانوني، المادة الجزائية، الشرعية الجنائية، الشرعية الإجرائية; Mots-clés : Sécurité juridique; droit pénal; légalité criminelle; légalité procédurale.